Bright X-ray galaxies in SDSS filaments - Tugay, A.V. (Advances in Astronomy and Space Physics, 2013)
Eighteen bright X-ray emitting galaxies were found in nearby filaments within the SDSS region. Basic X-ray spectral parameters were estimated for these galaxies using a power law model with photoelectric absorption. A close pair of X-ray galaxies was found.